DEVELOPING MUSHROOM GYMNASTIC INSTRUMENT PROTOTYPE FOR MEN’S ARTISTIC GYMNASTIC SPORT IN CENTRAL JAVA PROVINCE - Tommy Soenyoto (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
This study aims to develop mushroom gymnastic instrument for men’s artistic gymnastic athletes of junior and senior levels. The instrument is aimed at improving movement skills on horse saddle. Aside from its use as an exercise instrument for beginner, junior and senior levels of men’s artistic gymnastic athletes, this instrument can also be used for beginners’ level competition. This study used qualitative approach in which the data are collected from the initial step to the trial. The main procedure involved five steps: (1) the analysis of product development; (2) the development of initial product; (3) the expert validation; (4) the trial; and (5) the product revision. This study found that the mushroom gymnastic instrument can be used for men’s artistic gymnastic sport, particularly (1) for improving movement skill development on horse saddle for junior and senior athletes; (2) as an exercise instrument for beginner, junior and senior level of men’s artistic gymnastic athletes; (3) as an instrument used in competition for men’s artistic gymnastic for beginners’ level. Keywords: model development, prototype, mushroom gymnastics, men’s artistic gymnastics sport.